An observational prospective study of microbiological profiling in necrotizing fasciitis patients at tertiary care centre - Gupta, Madhusoodan; Varshney, Deepti (International Surgery Journal, 2021)
Background: Necrotizing fasciitis (NF) is described as the most aggressive form of skin and soft tissue infections. NF requires prompt diagnosis and urgent surgical procedure along with appropriate antibiotic coverage. Still NF has high morbidity and mortality. The aim of the study was to provide microbiological profile in necrotizing fasciitis patients and discover the appropriate antibiotics regimen to treat them early and appropriately. Methods: This observational prospective study was done of patients of necrotizing fasciitis between June 2016 to June 2018 in the department of plastic surgery in the central area of India. Results: In this study monomicrobial culture was positive in 66.7%, polymicrobial culture was positive 16.7% and no organism was found in 16.7% of patients. In our study most commonly, used antibiotic was colistine followed by tigecycline. Conclusions: Microbiological profiling and early use of sensitive antibiotic is a key to treat the necrotizing fasciitis. It renders the progression of disease and decreases the morbidity and mortality in necrotizing fasciitis.